Therapeutic relationship of salutogenic and playscape architecture : A suicide intervention within Sarawak youth community - Marzuki, Nurul Amirah; Mohd Noor, Mohd Zairul; D’Silva, Jeffrey Lawrence (Human Resource Management Academic Research Society, 2023)
Concerning the issue of increasing youth suicide in Sarawak, the Sarawak Government urged more studies on youth suicides in Sarawak. According to the Ministry of Health, the number of youths with mental health that leads to youth suicide has increased. This requires immediate intervention in architectural strategy. However, there is a lack of youth facilities and programs to tackle youth suicidal issues, especially in safe environments and resiliency in architecture. A literature review was carried out using various databases to examine this issue. The results provide pathways to include gaining insight into salutogenic architecture and playscape architecture affecting youth mental health issues in Sarawak and how it may help to detect the undiagnosed youth with mental health, especially with stress, anxiety and depression, and how this information might be used to help reduce future mental illness and suicide risk with the architectural explorations. This findings will benefit stakeholders to build a Sarawak youth community quality life. The future result will be produced in the framework or tangible output from the study.